Patient-centered outcomes on preparing for and undergoing gender-affirming phalloplasty: a qualitative, descriptive study - Daphna Harel; Asa Radix; Rachel Bluebond-Langner; Tenny R Zhang; Carolyn A Berry; Nnenaya Mmonu; Elijah Castle; Lee Zhao; Clarissa Ospina-Norvell; Mark Fendrick (BMJ Open)
Objective Despite increasing incidence of genital gender-affirming surgery (GGAS), there is no systematic method of evaluating patient perspectives. The objective of this study is to elucidate transgender and non-binary patient perspectives on gender-affirming phalloplasty/metoidioplasty via structured focus groups and determine convergent themes as the first step towards the development of a GGAS patient-reported outcome measure.Design We conducted a systematic qualitative study using a thematic content analysis of four focus groups from April 2021 to April 2022 comprising 8 patients undergoing phalloplasty/metoidioplasty and 10 patients post-phalloplasty/metoidioplasty. Focus groups were hosted virtually and recorded and transcribed. Discussions were guided by participant input and focused on goals, experiences, outcomes, satisfaction, and quality of life.Setting This volunteer but purposive sample of patients was recruited directly in clinic, via email, and via social media at NYU Langone Health (primary site), Callen-Lorde Community Health Center (New York, New York, USA) and the San Francisco Community Health Center.Participants We conducted focus groups with 18 patients before/after undergoing gender-affirming phalloplasty/metoidioplasty.Primary and secondary outcome measurements and statistical analysis Transcripts were uploaded into ATLAS.ti, a qualitative data analysis software that facilitates coding for thematic content analysis. We performed deductive and inductive coding to identify the themes that were clustered into overarching domains.Results The mean duration of focus groups was 81.5 min. Seven themes and 19 subthemes were constructed. The major themes were (1) goals, expectations, and priorities before/after surgery; (2) sexual function; (3) urinary function; (4) peer support; (5) decision-making; (6) mental health and quality of life; and (7) gender dysphoria. Of the major themes, those determined before the study included themes 1–3 and 6–7. Limitations include small sample size and bias in patient selection.Conclusions We conducted focus groups with 18 patients before/after undergoing gender-affirming phalloplasty/metoidioplasty. Mental health, quality of life, functional, and aesthetic outcomes are all critical to patients. Phalloplasty/metoidioplasty impact numerous aspects of patients’ lives. Experiential components of the surgical process, mental health, and quality of life are important metrics to consider in addition to functional and aesthetic outcomes.